Mengungkap Stigma Sosial dalam Praktek Parkir Liar (Bagaimana Stigma Masyarakat terhadap Parkir Liar di Kecamatan Panakukkang Kota Makassar) - Reskiawan, Muh Miftahul Nurul; W Suhaeb, Firdaus; Ashari, Ashari; Najamuddin, Najamuddin (Riwayat: Educational Journal of History and Humanities, 2025)
Social stigma against illegal parking is a negative view or judgment given by the community to illegal parkers because they are considered to disturb public order and cause unrest among the community. This study aims to (1) analyze how social stigma against illegal parking in Panakukkang District, Makassar City. (2) To analyze the factors influencing social stigma toward illegal parking in Panakukkang District, Makassar City. (3) To analyze the solutions proposed by the community to address illegal parking in Panakukkang District, Makassar City. The number of informants in this study was 10 people, determined by purposive sampling with the criteria of community members residing in Panakukkang District aged 19-40 years. The data collection techniques used were observation, interviews, and documentation. This research is qualitative and descriptive in nature. The results of this study show that: (1) How social stigma towards illegal parking in Panakukkang District, Makassar City is: a). Public Stigma, b). Structural Stigma, c). Self Stigma, d). Experienced Stigma. 2) Factors influencing social stigma toward illegal parking in Panakukkang District, Makassar City, are: a) Knowledge factor, b) Perception factor, c) Individual experience factor, d) Media factor. (3) Solutions proposed by the community in efforts to regulate illegal parking in Panakukkang District, Makassar City, are: a). Awareness and orderliness, b). Community participation and involvement.